1994
DOI: 10.1001/jama.1994.03520160070046
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Four Interventions for the Prevention of Low Back Pain

Abstract: There is limited evidence to recommend exercise to prevent low back pain in asymptomatic individuals, but there is insufficient evidence to recommend other prevention strategies. These conclusions should be viewed cautiously since they are primarily based on studies conducted in the workplace rather than in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
10

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(40 citation statements)
references
References 62 publications
0
30
0
10
Order By: Relevance
“…Earlier reviews on the topic concluded there was insufficient evidence to make recommendation for or against the use of back belts for the prevention of occupational low back injuries. 22,27,41,42 National Institute for Occupational Safety and Health (NIOSH), following the results of their most recent back belt study, concluded there was no evidence to support the use of back belts as a preventive measure. 38 This further supports their previous review and recommendations on back belt use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier reviews on the topic concluded there was insufficient evidence to make recommendation for or against the use of back belts for the prevention of occupational low back injuries. 22,27,41,42 National Institute for Occupational Safety and Health (NIOSH), following the results of their most recent back belt study, concluded there was no evidence to support the use of back belts as a preventive measure. 38 This further supports their previous review and recommendations on back belt use.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of consistent conclusions from the studies included for this review is not surprising given the conflicting laboratory evidence on how back belts are thought to prevent LBP. [22][23][24][25]27,43,49 Conclusions from studies reporting adverse effects were limited in both quantity and by the methods used. NIOSH has suggested that a false sense of security may accompany back belt use, which may lead to increased risk taking behaviors (such as excessive lifting).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our ®ndings thus underline the importance of physical inactivity as a risk factor for musculoskeletal morbidity. Physical inactivity may be also an important prognostic factor for chronicity of symptoms; interventions focusing on prevention or decreasing physical inactivity are reported to be successful, although the long-term eects are still unknown (Linton et al 1989;Lahad et al 1994). It seems, therefore, desirable to add a speci®c measurement of physical inactivity to the measurement of physical activities in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Randomised trials and epidemiological studies on exercises as a means of strengthening back and/or abdominal muscles and of improving ®tness have produced only limited evidence of a positive eect on low back morbidity (Lahad et al 1994; Koes et al 1991), and empirical evidence in particular of long-term eects of exercise is still lacking (Videman et al 1995). Alaranta et al (1987) showed that a high preoperative level of physical activity was linked to good 1-year results of surgery of lumbar intervertebral disc herniation in patients with a moderate to severe occupational handicap preoperatively, which indicates that participation in sports can also have a positive in¯uence on the possibilities of rehabilitating workers with musculoskeletal disorders (see also Linton et al 1989;Shephard 1991;Stewart et al 1994).…”
Section: Introductionmentioning
confidence: 99%